Efeito da cobertura do dossel ripário na estrutura de assembleias de macroinvertebrados de um afluente do Rio Caeté - FEITOSA, Jaqueline da Conceição Souza (2022)
The vegetation around water bodies, the riparian forest, plays a key role in maintaining aquatic systems. The macroinvertebrates that live in the stream environment benefit from the supply of allochthonous material from the riparian forest and are actively involved in the processing of organic matter and nutrient cycling. According to the means of food acquisition, morphology, and behavior they can be classified as shredder, collector, scraper, predator, and sucker-herbivore. In a tributary of Caeté River at Vila Camutá-PA, 5 points were sampled in which a total of 1578 individuals were found distributed in 32 macroinvertebrate taxa belonging to the classes Arachnida, Bivalvia, Clitellata, Insecta and Maxillopoda. At each point, the percentage of riparian cover was measured, and ranged from 36.55% to 80.86%. According to the cover factor created, points 1 (36.55%) and 2 (41.54%) were classified in medium cover (33% - 66%) and points 3 (80.86%), 4 (80.40%) and 5 (78.26%) in high cover (66% - 100%). Thus, there was no presence of points with low coverage (0 - 33%). The abundance data of taxa and functional groups were subjected to multivariate analysis to investigate the fauna structure in relation to canopy cover and to physicochemical variables of water and sediment. Leaf (g), Fine Sand (%), Total MO (g) and Medium Sand (%) were the variables most closely related to fauna and functional groups. The ordinations of the points with the taxonomic fauna and with the functional groups present similar conformations, with ellipses of the medium and high coverage overlapping demonstrating similarity between the two classes of habitats. The taxa Acari, Chironomidae, Copepoda, Ephemeroptera n.i., Hydroptilidae, Leptoceridae, Odontoceridae and Leptophlebiidae showed to be potential indicators of high cover. While Tipulidae, Coleoptera n.i., Gomphidae and Helicopsychidae taxa were shown to be potential indicators of medium cover. The two habitat classes differ significantly both in terms of the physicochemical variables and the structure of the taxonomic fauna, while for the functional groups, the difference is significant only between collection points. The results show that even changes in riparian forest cover may be associated with changes in the composition and abundance of the aquatic macroinvertbrate fauna.